2008
DOI: 10.1039/b811419f
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency EPR analysis of the positive polaron in I2-doped poly(3-hexylthiophene) and in poly[2-methoxy-5-(3,7-dimethyloctyloxy)]-1,4-phenylenevinylene

Abstract: The W-band continuous-wave electron paramagnetic resonance (EPR) analysis of chemically induced polarons in drop-cast and spin-coated polyphenylenevinylene-type and polythiophene-type polymer films reveals rhombic g tensors in both cases. The dependence of the W-band EPR signals on the orientation of the spin-coated films with respect to the magnetic field indicates a high degree of backbone alignment with the substrate and allows a partial assignment of the g tensor orientation. The derived molecular orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
113
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(134 citation statements)
references
References 39 publications
(62 reference statements)
15
113
1
Order By: Relevance
“…1(a)] are obtained by assuming two resonances with g ¼ 2:0028ð3Þ, a narrow pseudo-Voigtian line shape (FWHM ¼ 0:6ð1Þ mT) and a wider Gaussian component (1:5ð1Þ mT), with identical doubly integrated intensities [14]. The linewidths and g values agree with earlier EDMR and light-induced EPR measurements on polarons in PPV [12,15,16]. The g value excludes the possibility that PCBM anions (g ¼ 1:9995) are making a significant contribution to the spectrum [12].…”
supporting
confidence: 74%
“…1(a)] are obtained by assuming two resonances with g ¼ 2:0028ð3Þ, a narrow pseudo-Voigtian line shape (FWHM ¼ 0:6ð1Þ mT) and a wider Gaussian component (1:5ð1Þ mT), with identical doubly integrated intensities [14]. The linewidths and g values agree with earlier EDMR and light-induced EPR measurements on polarons in PPV [12,15,16]. The g value excludes the possibility that PCBM anions (g ¼ 1:9995) are making a significant contribution to the spectrum [12].…”
supporting
confidence: 74%
“…21 Note, that the g P iso value of the latter measured more accurately at W-band (94 GHz) EPR is equal to 2.00187. 26 These parameters were appeared to become weakly temperature dependent than those of the P3HT/PCBM composite. 21 As in case of other polymer/fullerene systems, 20,21 LEPR spectra of the P3HT/bis-PCBM bulk heterojunctions consists of two Lorentzian contributions of mobile polarons and bis-methanofullerene anion radicals in quasi-pairs P…”
Section: A Spectral Composition and G-factormentioning
confidence: 96%
“…This was confirmed later at millimeter waveband LEPR study of the P3HT/PCBM composite. Thus, it was shown that the spin of polarons photoinduced in the P3HT chains is also characterized by rhombic symmetry originating anisotropic g-factor with g xx = 2.0028, g yy = 2.0019, g zz = 2.0009 at W-band (94 GHz) EPR 26 and g xx = 2.00380, g yy = 2.00230, g zz = 2.00110 at D-band (130 GHz) EPR. 29 Spin distribution in the mC −• 61 anion radical embedded into P3HT matrix is also characterized by rhombic symmetry that leads to respective anisotropy of its g-factor with g xx = 2.00058, g yy = 2.00045, g zz = 1.99845.…”
Section: A Spectral Composition and G-factormentioning
confidence: 99%
“…Because of the higher resolution at W-band microwave frequencies, the LI-EPR spectrum now reveals distinct features. For comparison, the previously reported 32 W-band ESE-detected EPR blend (signal marked with asterisk in Fig. 6), together with a second feature at a higher g value (signal marked with # centered at g = 2.0045 in Fig.…”
Section: Polaron Detection By Electron Paramagnetic Resonancementioning
confidence: 99%